Public versus Private Borrowing: A Theory with Implications for Bankruptcy Reform - Detragiache, Enrica (Journal of Financial Intermediation, 1994)
A model is presented in which firms optimally finance investment with both public and private debt. The two instruments are perfect substitutes, except that private debt can easily be renegotiated in insolvency states while public debt cannot. The option to renegotiate is beneficial ex post, as it allows the firm to avoid inefficient liquidation, but ex ante it may worsen asset substitution. The welfare effects of alternative bankruptcy regimes are then compared, taking into account that firms modify their financing decision in response to the regime change. Some suggestions for reforming Chapter 11 of the U.S. bankruptcy code are presented. Journal of Economic Literature Classification Numbers: G32, G33, K2.